Experimental study on large deformation of free surface during water exit of a sphere. (1st August 2017) - Wu, Q.G.; Ni, B.Y.; Bai, X.L.; Cui, B.; Sun, S.L.
Abstract: During water exit of a solid body, the free surface is disturbed and deformed. To study the free-surface deformation and its dynamic change such as breakup, a set of water-exit equipment was designed and a series of experiment on water exit of a sphere were conducted. High-speed photographic technologies were adopted to capture the whole process of water exit and the large deformation of the free surface. Work was divided into forced water exit and free water exit. In the forced water exit, either a fully-submerged or a partially-submerged sphere was pushed out of water at a constant speed. The influence of the velocity or Froude number was investigated. In the free water exit, an initially static sphere with an equivalent density smaller than water was released underwater by using an electromagnet. Water exit at different initial submergence depth was conducted. Velocity and acceleration of the light sphere are analysed. Highlights: A set of water-exit equipment is designed to study large free-surface deformation. Free-surface spike and the water column following sphere rise with body velocity The upward fluid force rises before falls downwards in high-speed free water exit. Air may be trapped inside the water column at the end of high-speed free water exit.